MALIGNANT HYPERTENSION WITH PREDOMINANT KIDNEY DAMAGE - N. D. Lapochkina; S. S. Mamedguseyinova; L. V. Korsakova; V. I. Vechorko; S. M. Otarova; I. G. Gordeev (Российский кардиологический журнал)
The article is on a clinical case of malignant arterial hypertension in predominant kidney damage in a young man with disease anamnesis lasting 17 years. Recent data on the disorder provided, aspects of its management complexity that do make to regard the problem far from solution.